93.9k views
1 vote
Multiply binomails (x + 2) (3x+1)

2 Answers

5 votes

Answer:

3x² + 7x + 2

Explanation:

Each term in the second factor is multiplied by each term in the first factor, that is

x(3x + 1) + 2(3x + 1) ← distribute both parenthesis

= 3x² + x + 6x + 2 ← collect like terms

= 3x² + 7x + 2

User Mikkelbreum
by
5.4k points
5 votes

Answer:

The answer is 3x^2+7x+2

Explanation:

Multiply each term of the second bracket with the first bracket.

We can write:

(x+2)(3x+1)= 3x(x+2)+1(x+2)

By multiplying the terms we get:

=3x^2+6x+x+2

Now simplify by combining like terms:

=3x^2+7x+2

Thus the answer is 3x^2+7x+2....

User WastedSpace
by
6.4k points